Perilaku Lintasan Tegangan (Stress Path) Pada Tanah Gambut Rawaseragi Lampung - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Peat is soil with a high organic content, water content, and compressibility, and also low bearing capacity. Peat have difference behavior and characteristic among one site with the other site. Stress path method can be used to represent the behavior of peat soil during the loading. This paper present the behavior of stress path on Rawaseragi Lampung peat soil using triaxial apparatus 36 mm dia, and 76 min height of specimen. The consolidated drained and consolidated undrained triaxial tests were conducted on sample of Lampung peat, with the variation of cell pressure 50 kPa, 100 kPa, 200 kPa and, 400 kPa. The results of triaxial test analysis with stress path method to find soil parameters show that Lampung peat are described as fibrous peat. The maximum deviator stress reached at strain 10% -16% and 9% - 16% for consolidated drained and consolidated undrained, respectively. Based on the critical 'state line Lampung peat is near to normally consolidated, with the intersection value of critical state line to q axis is equal to 19,459 kPa and pore pressure change is always positive (Au > 0). Soil parameters were found to be : M = 0,8668